Companies income tax and petroleum profits tax in Nigeria - Ani, A. A; Abdulalhi, Z.A. (Ibadan : University Press Ltd., 1989)
This book consist of numerous changes in the laws governing companies income tax and petroleum profits tax as well as the current practice in the petroleum industry concerning tax and royalty obligations.
Includes index.
osa 04/07/2017
Loans
Keywords: Corporations; Petroleum; Excess profits tax; Nigeria